Effectiveness and Cost-effectiveness of Opportunistic Screening and Stepped-care Interventions for Older Alcohol Users in Primary Care. (8th September 2017) - Coulton, Simon; Bland, Martin; Crosby, Helen; Dale, Veronica; Drummond, Colin; Godfrey, Christine; Kaner, Eileen; Sweetman, Jennifer; McGovern, Ruth; Newbury-Birch, Dorothy; Parrott, Steve; Tober, Gillian; et al.
Abstract: Aims: To compare the clinical effectiveness and cost-effectiveness of a stepped-care intervention versus a minimal intervention for the treatment of older hazardous alcohol users in primary care. Method: Multi-centre, pragmatic RCT, set in Primary Care in UK. Patients aged ≥ 55 years scoring ≥ 8 on the Alcohol Use Disorders Identification Test were allocated either to 5-min of brief advice or to 'Stepped Care': an initial 20-min of behavioural change counselling, with Step 2 being three sessions of Motivational Enhancement Therapy and Step 3 referral to local alcohol services (progression between each Step being determined by outcomes 1 month after each Step). Outcome measures included average drinks per day, AUDIT-C, alcohol-related problems using the Drinking Problems Index, health-related quality of life using the Short Form 12, costs measured from a NHS/Personal Social Care perspective and estimated health gains in quality adjusted life-years measured assessed EQ-5D. Results: Both groups reduced alcohol consumption at 12 months but the difference between groups was small and not significant. No significant differences were observed between the groups on secondary outcomes. In economic terms stepped care was less costly and more effective than the minimal intervention. Conclusions: Stepped care does not confer an advantage over a minimal intervention in terms of reduction in alcohol use for older hazardous alcohol users in primary care. However, stepped care has a greater probability of being more cost-effective. Trial Registration: Current controlled trials ISRCTN52557360. Short summary: A stepped care approach was compared with brief intervention for older at-risk drinkers attending primary care. While consumption reduced in both groups over 12 months there was no significant difference between the groups. An economic analysis indicated the stepped care which had a greater probability of being more cost-effective than brief intervention.